Pharmacometrics: Opportunity for Reducing Disease Burden in the Developing World: The Case of Africa. (28th August 2013) - Pillai, G; Davies, G; Denti, P; Steimer, J‐L; McIlleron, H; Zvada, S; Chigutsa, E; Ngaimisi, E; Mirza, F; Tadmor, B; Holford, NHG
Abstract : Pharmacometricians are virtually nonexistent in Africa and the developing world. The unrelenting burden of infectious diseases, which are often treated using medicines with narrow effectiveness and safety dose ranges, and the growing prevalence and recognition of non‐communicable diseases represent significant threats for the patients, although affording an opportunity for advancing science. This article outlines the case for pharmacometricians to redirect their expertise to focus on the disease burden affecting the developing world. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e69; doi:10.1038/psp.2013.45 ; published online 28 August 2013